Improving the energy efficiency of container stack assemblydisassembly operations at container terminal yard - Kovalenko, Valentyn; Turchyn, Olha; Alieksieiev, Volodymyr; Stryzhak, Vsevolod; Strelkov, Maksym; Poliakov, Oleksii (Національний технічний університет "Харківський політехнічний інститут", 2024)
Container storage in the yard decouples fluctuating incoming and outgoing container flows on container terminals and is an important element of the terminal process chain. The efficiency of handling operations in storage area, such as stacking and extraction of containers, has a significant influence on the overall terminal performance. In this respect, optimization of these processes, such as minimization of numerous unproductive movements of surrounding containers, which impede their immediate accessibility, is of particular interest. The relevant problems are well developed in mathematical terms. Optimizing algorithms mainly involve the use of heuristic/hyper-heuristic rules. However, only a small amount of this work focuses on the energy aspect of this problem. This article focuses on the most general approaches to minimizing energy consumption in container stacking operations. The performed analysis of energy consumption of the yard RTG crane for different working movements showed the prevalence of energy consumption when lifting containers. In this regard, attention is drawn to the importance of including in the optimization analysis in addition to the process of retrieving containers from the stack - the process of stack formation. Minimizing the level of the stack's center of gravity just before disassembling can be considered as a goal. Due to the complexity of the problem, an attempt to simplify the rules of container placement is made, taking into account some features of the energy approach. A possible generalized version of the arrangement scheme and the rule of removal of all containers are considered.

Зберігання контейнерів на майданчику дозволяє відокремити коливання вхідних і вихідних потоків контейнерів на терміналах і є важливим елементом ланцюга процесів терміналу. Ефективність операцій у зоні зберігання, таких як штабелювання та вилучення контейнерів, значно впливає на загальну продуктивність терміналу. Оптимізація цих процесів, зокрема мінімізація зайвих переміщень контейнерів, які перешкоджають доступу до них, має велике значення. Хоча ці проблеми добре описані математично, лише незначна частина робіт фокусується на енергетичному аспекті. У статті розглядаються загальні підходи до зниження енергоспоживання під час операцій штабелювання. Аналіз енергоспоживання крана RTG показав, що основна частина енергії витрачається на підйом контейнерів. Тому доцільно включити в оптимізацію не тільки процес вилучення контейнерів, але й процес їхнього розміщення. Мета – мінімізувати висоту центра ваги штабеля перед його розбиранням. Через складність задачі пропонується спрощення правил розміщення контейнерів з урахуванням енергетичного підходу, а також загальна схема їхнього розташування і видалення.
Підвищення енергоефективності операцій зі збирання-розбирання штабелів контейнерів на майданчику контейнерного терміналу
Keywords: Container Relocation Problem; energy efficiency; RTG crane; проблема переміщення контейнерів; енергоефективність; кран RTG